Evaluasi Penggunaan Fingerprint Sebagai Upaya Pencegahan Fraud Pada Peserta BPJS Rawat Jalan Di RSIA X Kupang - Maria Sumiati Amabi; Dwi Nur Siti Marchamah; Wahyuni Arumsari (Indonesian Journal of Health Community, 2025)
Since the National Health Insurance program was launched, BPJS Kesehatan has faced many challenges, one of which is the potential for fraud. BPJS has collaborated to develop fingerprint innovations by implementing a digitalization process for eligibility assurance. The purpose of this study was to review the effectiveness of fingerprint use as a fraud prevention effort in outpatient BPJS participant services at RSIA X Kupang. The research method was qualitative with interviews, observation, and documentation. The study was conducted from October to December 2024. A review of the implementation of fingerprint use in outpatient BPJS patient services at RSIA X showed a significant decrease in potential fraud cases compared to the previous year, when fingerprints were not implemented. The percentage of potential fraud patients who came for outpatient treatment using another participant's BPJS participant card in 2024 experienced a significant decrease, where out of a total of 14,817 outpatients in 2024, there were 2 patients, or equal to 0.01% who had the potential for fraud. The evaluation process must be carried out correctly and precisely to maximize the quality of service in the use of fingerprints.